A halloysite composite hemostatic material and its preparation method and application

By hydroxylation modification on elosteite and loading the aggregation of luminescent nanoparticles, the elosteite composite hemostatic material was prepared, which solved the problem of exothermic heat during the hemostatic process of existing hemostatic materials, and improved the hemostatic performance and antibacterial effect. , achieving improvements in biocompatibility and safety performance.

CN116570756BActive Publication Date: 2025-02-18CHINA UNIV OF GEOSCIENCES (WUHAN)
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310530468.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-10
Publication Date
2025-02-18
Estimated Expiration
2043-05-10

AI Technical Summary

Technical Problem

External heat exothermic problems in existing inorganic hemostatic materials such as zeolites are difficult to solve during the hemostatic process. Although Elosite has excellent hemostatic properties, there is still room for improvement in its functional modification and load.

Method used

Using hydroxylated modified Elolite as a carrier, the luminescent nanoparticles are loaded to collect the aggregation-induced luminescent nanoparticles, and the hydroxylated modified Elolite suspension is mixed with the aggregation-induced luminescent nanoparticles solution to prepare the luminescent composite Hemostatic material.

Benefits of technology

It significantly improves the hemostatic effect, gives Elosite antibacterial properties, and the preparation method is simple and easy to operate, which is conducive to large-scale production. The obtained materials are characterized by good biocompatibility, high safety performance and good antibacterial effects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116570756B_ABST
    Figure CN116570756B_ABST
Patent Text Reader

Abstract

The present invention discloses a halloysite composite hemostatic material and a preparation method and application thereof. The present invention uses hydroxylated modified halloysite as a carrier and loads aggregation-induced luminescent nanoparticles. The preparation method comprises the following steps: configuring the modified halloysite into a suspension; configuring an aggregation-induced luminescent nanoparticle solution; mixing the surface hydroxylated halloysite suspension with the aggregation-induced luminescent nanoparticle solution under certain temperature and oscillation speed conditions, centrifuging the obtained material, and freeze-drying the precipitate to obtain an aggregation-induced luminescent nanoparticle modified halloysite composite, i.e., a halloysite composite hemostatic material. In the present invention, the surface hydroxylated modified halloysite is used to significantly improve the hemostatic effect. Furthermore, by functionalizing a small amount of loaded aggregation-induced luminescent nanoparticles, in addition to giving the halloysite antibacterial properties, its hemostatic properties are further improved. Finally, a halloysite composite hemostatic material with good biocompatibility, high safety performance, and good antibacterial effect is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of hemostatic materials, and in particular to a halloysite composite hemostatic material and a preparation method and application thereof. Background Art

[0002] The development of hemostatic materials with richer performance, better hemostatic effect, more biosafety and low price has always been the focus of research. Inorganic hemostatic materials, especially aluminosilicate hemostatic agents such as halloysite, zeolite, kaolin and montmorillonite, are popular due to their high efficiency, operability, cost-effectiveness and minimal tissue reactivity. In addition, zeolite has good hemostatic effect, but the exothermic problem of its hemostatic process has been difficult to overcome.

[0003] For thousands of years, the excellent hemostatic performance and in vivo safety of Halloysite nanotubes (HNTs) have been verified by clinical cases. Studies have found that the procoagulant ability of HNTs is between zeolite and montmorillonite, and is about 2.3 times that of kaolin. In addition, researchers also found that the water absorption rate of HNTs is close to that of zeolite (about 80% of its own volume), which is significantly higher than that of montmorillonite and kaolin. Therefore, it is of great significance to further functionalize and load halloysite to achieve synergistic enhancement of its hemostatic effect and enrich its functions, especially in the field of wound healing. Summary of the invention

[0004] The purpose of the present invention is to provide a halloysite composite hemostatic material and a preparation method and application thereof in view of the above-mentioned deficiencies in the prior art.

[0005] The halloysite composite hemostatic material of the present invention uses hydroxylated modified halloysite as a carrier and is loaded with aggregation-induced luminescent nanoparticles. The aggregation-induced luminescent nanoparticles are TTPy, and the structural formula is:

[0006]

[0007] Furthermore, the hydroxylated modified halloysite is hydroxylated modified tubular halloysite.

[0008] Further, the method for preparing hydroxylated modified halloysite is as follows:

[0009] S1: First, halloysite is dispersed with deionized water, and then sodium hexametaphosphate ((NaPO3)6) is added. Then, the pH is adjusted using a NaOH solution, and finally, the precipitate is allowed to stand and dried to obtain purified halloysite;

[0010] S2: The purified halloysite is impregnated with HCl solution, and the mixture is washed with ultrapure water until the washing liquid is neutral, and finally dried and ground to obtain surface hydroxylated modified halloysite, which is marked as HNTs.

[0011] Furthermore, the concentration of the NaOH solution is 0.1-1 mol·L -1 ,; the mass ratio of halloysite to (NaPO3)6 solution is (0.1-20):1; the concentration of the HCl solution is 0.1-4 mol·L -1 .

[0012] Further, the pH was adjusted to 11-12 with NaOH solution.

[0013] A method for preparing the halloysite composite hemostatic material as described above, comprising dispersing the surface hydroxylated modified halloysite in deionized water and ultrasonically preparing a uniformly dispersed hydroxylated modified halloysite suspension;

[0014] The aggregation-induced luminescence nanoparticles are dissolved in DMSO to prepare an aggregation-induced luminescence nanoparticle solution;

[0015] The surface hydroxylated halloysite suspension is mixed with the aggregation-induced luminescent nanoparticle solution under certain temperature and oscillation speed conditions, the obtained material is centrifuged, and the precipitate is freeze-dried to obtain the aggregation-induced luminescent nanoparticle modified halloysite composite, namely the halloysite composite hemostatic material.

[0016] Furthermore, the mass ratio of the aggregation-induced emission nanoparticles to the halloysite is (0.5-2.0):100.

[0017] Furthermore, the concentration of the aggregation-induced luminescence nanoparticles is 0.01-10 mg / mL.

[0018] An application of the halloysite composite hemostatic material as described above is to prepare a suspension of the halloysite composite hemostatic material, then immerse a medical nonwoven fabric in the evenly stirred suspension, immersing the upper and lower edges once respectively; pressing and drying the soaked gauze to obtain the halloysite hemostatic gauze.

[0019] Furthermore, the concentration range of the halloysite composite hemostatic material suspension is 0.1-100 mg / mL.

[0020] The surface hydroxylated halloysite used in the present invention can significantly improve the hemostatic effect. Furthermore, by functionalizing a small amount of loaded aggregation-induced luminescent nanoparticles, in addition to giving the halloysite antibacterial properties, its hemostatic performance is further improved. Ultimately, a halloysite composite hemostatic material with good biocompatibility, high safety performance and good antibacterial effect is obtained. Moreover, the preparation method of the present invention has simple steps, is easy to operate, and is conducive to large-scale production.

[0021] The invention combines the medical non-woven fabric with the halloysite composite hemostatic material by infiltration to prepare a medical hemostatic gauze product with good hemostatic performance, good biocompatibility, high safety performance, antibacterial properties and a simple preparation method, which is conducive to industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 The structure of the aggregation-induced luminescence nanoparticles;

[0023] Figure 2 The morphology images of Raw HNTs, Example 1, and Example 2;

[0024] Figure 3 Infrared results of Raw HNTs, Example 1, and Example 2;

[0025] Figure 4 Photos of blank gauze of the present invention and gauze products prepared in Examples 3-5;

[0026] Figure 5 Surface morphology of the blank gauze of the present invention, the halloysite composite hemostatic gauze prepared in Examples 3-5, and Quikclot gauze (the main component of which is kaolinite);

[0027] Figure 6 The cross-sectional morphology diagrams of the blank gauze of the present invention and the halloysite composite hemostatic gauze and Quikclot gauze prepared in Examples 3-5;

[0028] Figure 7a , 7b The antibacterial results of the blank gauze and the halloysite composite hemostatic gauze prepared in Examples 3-5;

[0029] Figure 8 The cytotoxicity graphs of the blank gauze and the halloysite composite hemostatic gauze prepared in Example 3-5;

[0030] Fig. 9 This is a graph showing the hemostatic time of the liver in animals of the blank gauze of the present invention and the halloysite composite hemostatic gauze and Quikclot gauze prepared in Examples 3-5;

[0031] Fig.10 The graphs show the amount of liver bleeding in animals of the blank gauze of the present invention and the halloysite composite hemostatic gauze and Quikclot gauze prepared in Examples 3-5. DETAILED DESCRIPTION

[0032] The following are specific embodiments of the present invention and the accompanying drawings to further describe the technical solution of the present invention, but the present invention is not limited to these embodiments.

[0033] The halloysite in the examples of this specification is a halloysite nanoclay product produced by Sigma-Aldrich Company of the United States, with a molecular formula of Al2Si2O5(OH)4·2H2O, a molecular weight of 294.19, and a density of 2.53 g / cm 3 .

[0034] The aggregation-induced luminescence nanoparticles in the embodiments and are TTPy, which are prepared by Guangzhou Carbon Water Biotechnology Co., Ltd. according to the structural formula designed by the applicant, and have the following structure: Figure 1 shown.

[0035] Halloysite Preparation

[0036] In the preparation stage of the halloysite raw material, the method comprises the following steps: the halloysite is fully ground and marked as RawHNTs.

[0037] Preparation of Aggregation-Induced Emission Nanoparticle Suspension

[0038] 10 mg of aggregation-induced luminescence nanoparticles were dissolved in 1 mL of DMSO to obtain a 10 mg / mL aggregation-induced luminescence nanoparticle solution.

[0039] Preparation of modified halloysite

[0040] Embodiment 1:

[0041] Halloysite modification: First, 10 g of halloysite (Raw HNTs) was dispersed in 1000 mL of deionized water with magnetic stirring for about 1 hour, and then ultrasonic treatment was performed for about 1 hour. The above process was repeated until the Raw HNTs were fully dispersed in the solution. Next, 0.5 g of sodium hexametaphosphate ((NaPO3)6) was added to the mixture and stirred vigorously for about 1 hour to completely disperse the (NaPO3)6. Then, 1 mol·L -1 The pH of the mixture was adjusted to about 11 with NaOH solution. After standing for about 3 hours, the suspension was filtered to obtain a solid precipitate, which was dried at 60°C for 24 hours to obtain purified halloysite. The purified halloysite was treated with 4 mol·L -1 The mixture was immersed in HCl at room temperature for 3 h, and then washed with ultrapure water for several times until the washing liquid was neutral. Finally, the modified halloysite was obtained by drying and grinding, which was labeled as HNTs.

[0042] Preparation of Aggregation-Induced Emission Nanoparticle-Modified Halloysite Composites

[0043] Embodiment 2:

[0044] 693 μL of deionized water was added to 267 μL of 100 mg / mL HNTs suspension for dispersion, and then 40 μL of 10 mg / mL aggregation-induced luminescence nanoparticle solution was added. The resulting 1 mL of the mixed solution was placed in a constant temperature mixer and mixed at 37°C, 1000 rpm, for 3 hours. The resulting material was centrifuged at 14000 rpm for 10 minutes, and the precipitate was freeze-dried for 24 hours to obtain an aggregation-induced luminescence nanoparticle-modified halloysite composite, labeled as HNTs-TTPy.

[0045] Figure 2 The morphology of Raw HNTs, Example 1, and Example 2 is shown in Figure 2. Figure 2 It can be seen that compared with the Raw HNTs, the sizes of Examples 1 and 2 are reduced and the exposed surfaces are increased. Figure 3 The infrared results of Raw HNTs, Example 1, and Example 2 are shown in Figure 2. Figure 3 It can be seen that compared with Raw HNTs, Example 1 has a higher Si-O stretching vibration peak (1099 cm -1 、1018cm -1 ), the bending vibration peak of Al-OH (920cm -1 ), Si-O, Al-O stretching vibration peaks (548, 461 cm -1 ) is significantly enhanced, indicating that the number of hydroxyl groups on the halloysite surface increases. The characteristic peak of Example 3 is lower than that of Example 2, which may be caused by the combination of aggregation-induced luminescent nanoparticles on the halloysite surface.

[0046] Preparation of Halloysite Hemostatic Gauze

[0047] Embodiment 3:

[0048] 3 mL of 100 mg / mL Raw HNTs suspension was placed in a beaker, and 27 mL of deionized water solution was added. The solution was stirred at 500 rpm for 1 h to make it uniform. A piece of non-woven gauze (area 10*9.5 cm) was cut out. 2 ), immerse the gauze directly in the uniform suspension to make the powder adhere to the surface of the gauze, and immerse the upper and lower sides of the gauze once, with a total time of about 2s. Place the soaked gauze on a roller press and press it once. The spacing between the upper and lower rollers of the roller press is 0.05mm to enhance the adhesion between the powder material and the non-woven fabric. Finally, the pressed non-woven gauze is hung with a dovetail clip and air-dried in an oven at 60°C to obtain a composite gauze of aggregation-induced luminescent nanoparticles modified halloysite, which is marked as Raw HNTs Gauze.

[0049] Embodiment 4:

[0050] 3 mL of 100 mg / mL HNTs suspension was placed in a beaker, and 27 mL of deionized water solution was added. The solution was stirred at 500 rpm for 1 h to make it uniform. A piece of non-woven gauze (area 10*9.5 cm 2 ), immerse the gauze directly in the uniform suspension to make the powder adhere to the surface of the gauze, and immerse the upper and lower sides of the gauze once, with a total time of about 2s. Place the soaked gauze on a roller press and press it once. The spacing between the upper and lower rollers of the roller press is 0.05mm to enhance the adhesion between the powder material and the non-woven fabric. Finally, the pressed non-woven gauze is hung with a dovetail clip and air-dried in an oven at 60°C to obtain a composite gauze of aggregation-induced luminescent nanoparticles modified halloysite, marked as HNTs Gauze.

[0051] Embodiment 5:

[0052] 3 mL of 100 mg / mL HNTs suspension was placed in a beaker, and 26.55 mL of deionized water solution was added. 10 mg / mL of aggregation-induced luminescence nanoparticle solution was added under stirring at 500 rpm. The solution was stirred for 1 h to make it uniform. A piece of non-woven gauze (area 10*9.5 cm 2 ), immerse the gauze directly in the uniform suspension to make the powder adhere to the surface of the gauze, and soak the upper and lower sides of the gauze once, with a total time of about 2s. Place the soaked gauze on a roller press and press it once. The spacing between the upper and lower rollers of the roller press is 0.05mm to enhance the adhesion between the powder material and the non-woven fabric. Finally, the pressed non-woven gauze is hung with a dovetail clip and air-dried in an oven at 60°C to obtain a composite gauze of aggregation-induced luminescent nanoparticles modified halloysite, marked as HNTs-TTPy Gauze.

[0053] Figure 4 This is a photo of a gauze product obtained by infiltration of the halloysite composite hemostatic material suspension. As shown in the figure, the color of the gauze has become significantly darker, indicating that the halloysite composite hemostatic material has been successfully loaded on the gauze. Figure 5 and Figure 6 ,It can be seen from the surface morphology and cross-sectional view of the hemostatic gauze that in Examples 3-5, the tubular halloysite composite hemostatic material is successfully loaded on the gauze, while in Quickclot, the loaded material is kaolinite with a flake morphology.

[0054] The loading amount of hemostatic material in the gauze products of Examples 3-5 is shown in Table 1.

[0055] Table 1 Loading amount of HNTs-TTPy gauze hemostatic material

[0056] Case Mass before loading (g) Loaded mass (g) Loading capacity (g) <![CDATA[Load density (g / m 2 )]]> Example 3 0.5119 0.5330 0.0211 2.2211 Example 4 0.4951 0.5139 0.0188 1.9789 Example 5 0.5055 0.5608 0.0553 5.8211

[0057] In vitro antibacterial test:

[0058] Staphylococcus aureus (ATCC 25923) was used as a Gram-positive bacteria model to evaluate the antibacterial activity of the samples. A single strain of Staphylococcus aureus was dispersed in 5 mL of Luria–Bertani liquid medium and shaken at 37 °C for 8 h to obtain an initial bacterial concentration of 2 × 10 6 CFU / mL. Subsequently, the bacterial suspension was serially diluted 10 3 Then, 1 mL of the diluted bacterial suspension was mixed with 20 mg of shredded gauze, and the mixed bacterial sample was incubated in the dark for 5 min, and then heated at 100 mw / cm 2 Irradiate under white light for 30 minutes. Then dilute the bacterial suspension 10 times with PBS, spread 100uL of the diluted bacteria on the corresponding solid agar plate, and incubate at 37℃ for 14-16h. The bacterial survival rate is used as an indicator to evaluate the antibacterial activity of the material against bacteria.

[0059] Bacterial survival rate = average number of colonies in the sample / average number of colonies in the control group × 100%

[0060] The antibacterial effects of blank gauze and Examples 3-5 on Staphylococcus aureus are shown in Figure 7a ,b. From Figure 7a ,b The results of bacterial plating and bacterial counting show that, compared with blank gauze, Raw HNTs Gauze and HNTs Gauze have a weak bactericidal effect on Staphylococcus aureus, which may be related to the contact and adhesion of clay minerals on the bacterial surface. Since bacteria are isolated from the external environment, the normal metabolism of bacteria is affected, which further leads to the death of bacteria. HNTs-TTPyGauze has a significant antibacterial effect after illumination, which indicates that after the clay mineral halloysite is compounded with TTPy, a large amount of active oxygen can be produced under illumination, thereby effectively killing bacteria.

[0061] Cytotoxicity assay

[0062] This experiment uses the Cell Counting Kit-8 (CCK-8) method to analyze the cytotoxicity of samples using human immortalized fibroblasts (BJ cells) as the research object. Use RPMI-1640 basic medium, 1% double antibody, and 10% fetal bovine serum to prepare a complete medium for culturing BJ cells. Take the normally frozen BJ cells and shake them continuously in a 37°C water bath until they are thawed. Pipette 1mL of BJ cell freezing solution and add it to a 15mL centrifuge tube filled with 10mL of complete medium. Shake to mix, centrifuge at 1000rpm for 5min, remove the supernatant and resuspend the cells with complete medium, and transfer the cell suspension to a culture dish. After the cells are cultured until they are in a good state of adherent growth, use trypsin to digest them and resuspend the cells so that they are detached from the adherent state. Adjust the density of the cell suspension to 1×10 per well. 4 The cells were seeded in 96-well plates at a cell density of 100 μl and incubated at 37°C with 5% CO 2 Incubate in a cell culture incubator until the cells are well adhered to the wall and produce. Discard the original culture medium, add 100 μL of fresh complete culture medium to the control well, and add 100 μL of culture medium containing samples of different concentrations to the test wells. Continue to culture for 24 hours and measure the cytotoxicity, that is, add complete culture medium containing 10% CCK-8 reagent to each well, continue to culture for 1 hour, and measure the absorbance (OD) value of the culture medium at 450nm by an enzyme marker. At the same time, the wells without added sample materials are used as blank control groups, and the cell survival rate is calculated by measuring the absorbance. The cell survival rate is calculated as follows:

[0063] Cell survival rate = (OD experimental well - OD blank well) / (OD control well - OD blank well) × 100%

[0064] The toxicity of blank gauze and Examples 3-5 was evaluated by setting a concentration gradient of 10, 25, and 50 μg / mL. The test results of the experiment are as follows: Figure 8 As shown. In the cytotoxicity level, a cell survival rate greater than 75% is designated as reaching the first biosafety level. The cell survival rates of the blank gauze and Examples 3-5 were all higher than 75% within the experimental concentration range, indicating that both HNTs Gauze and HNTs-TTPy Gauze have good biocompatibility.

[0065] In vivo liver hemostasis assay:

[0066] Male Kunming mice aged 8-10 weeks were selected and randomly divided into groups according to body weight, with 5 mice in each group. The anesthetized mice were fixed, the abdominal cavity of the mice was opened, and a wound of about 1 cm was cut on the left lobe of the liver with a scalpel. The bleeding left lobe of the liver was covered with a gauze sample, and the hemostasis time was recorded. The weight change of the gauze sample was weighed to calculate the amount of bleeding. The hemostasis time and bleeding amount of each case are shown in Table 2. Fig. 9 and Fig.10 shown.

[0067] Table 2 Bleeding time and amount of HNTs-TTPy hemostatic gauze

[0068] Case Material Hemostasis time (s) Amount of bleeding (mg) Control group No material added 89.67±10.69 500.90±210.30 Blank gauze Additive-free gauze 90.67±30.66 504.09±152.70 Example 3 Gauze with RawHNTs added 63.33±4.51 489.96±33.31 Example 4 Gauze with HNTs added 54.33±5.13 453.12±43.69 Example 5 Gauze with HNTs-TTPy added 44.00±1.73 472.90±104.95 Quikclot Quikclot Gauze 44.00±3.46 455.00±64.29

[0069] From Table 2, Fig. 9 and Fig.10 It can be seen that compared with Example 3 (Raw HNTs Gauze), the hemostatic time of HNTs Gauze in Example 4 is shortened, which indicates that the surface hydroxylation of halloysite may improve the hemostatic performance by increasing the exposed hydroxyl groups on the surface of halloysite. The hemostatic performance of HNTs-TTPy Gauze in Example 5 is further improved compared with Examples 3 and 4. This shows that the increase in the exposed hydroxyl groups on the surface of halloysite, in addition to improving the hemostatic performance, can also increase the load of aggregation-induced luminescent nanoparticles, and the positively charged aggregation-induced luminescent nanoparticles can reduce red blood cell hemolysis due to the neutralization of part of the negative charge on the surface of HNTs, thereby improving the biocompatibility of HNTs-TTPy Gauze and enhancing the hemostatic performance. Therefore, the surface hydroxylated halloysite and TTPy in HNTs-TTPy Gauze can achieve a synergistic improvement in hemostatic performance. In addition, the hemostatic speed of HNTs-TTPy Gauze is comparable to that of the existing hemostatic gauze (Quikclot) on the market. Compared with the control group, it significantly improves the hemostatic speed, reduces the amount of bleeding, and has excellent antibacterial properties.

[0070] For matters not mentioned above, the prior art applies.

[0071] Although some specific embodiments of the present invention have been described in detail through examples, those skilled in the art should understand that the above examples are for illustration only and are not intended to limit the scope of the present invention. Those skilled in the art to which the present invention belongs may make various modifications or supplements to the specific embodiments described or replace them in a similar manner, but they will not deviate from the direction of the present invention or exceed the scope defined by the attached claims. Those skilled in the art should understand that any modifications, equivalent substitutions, improvements, etc. made to the above embodiments based on the technical essence of the present invention should be included in the protection scope of the present invention.

Claims

1. A halloysite composite hemostatic material, characterized in that: Hydroxylated modified halloysite is used as a carrier, and aggregation-induced luminescence nanoparticles are loaded. The aggregation-induced luminescence nanoparticles are TTPy, and the structural formula is: ; The method for preparing hydroxylated modified halloysite is as follows: S1: First, halloysite is dispersed with deionized water, and then sodium hexametaphosphate ((NaPO3)6) is added. Then, the pH is adjusted using a NaOH solution, and finally, the precipitate is allowed to stand and dried to obtain purified halloysite; S2: The purified halloysite is impregnated with HCl solution, and the mixture is washed with ultrapure water until the washing liquid is neutral, and finally dried and ground to obtain surface hydroxylated modified halloysite, which is marked as HNTs.

2. The halloysite composite hemostatic material according to claim 1, characterized in that: The hydroxylated modified halloysite is hydroxylated modified tubular halloysite.

3. The halloysite composite hemostatic material according to claim 2, characterized in that: The concentration of the NaOH solution is 0.1-1 mol·L -1 ,; the mass ratio of halloysite to (NaPO3)6 solution is (0.1-20):1; the concentration of the HCl solution is 0.1-4 mol·L −1 .

4. The halloysite composite hemostatic material according to claim 1, characterized in that: Adjust the pH to 11-12 with NaOH solution.

5. A method for preparing the halloysite composite hemostatic material according to any one of claims 1 to 4, characterized in that: Dispersing the surface hydroxylated modified halloysite in deionized water and ultrasonically preparing a uniformly dispersed hydroxylated modified halloysite suspension; The aggregation-induced luminescence nanoparticles are dissolved in DMSO to prepare an aggregation-induced luminescence nanoparticle solution; The surface hydroxylated halloysite suspension was mixed with the aggregation-induced luminescence nanoparticle solution at 37°C and 1000 rpm, the obtained material was centrifuged, and the precipitate was freeze-dried to obtain the aggregation-induced luminescence nanoparticle modified halloysite composite, namely the halloysite composite hemostatic material.

6. The preparation method according to claim 5, characterized in that: The mass ratio of the aggregation-induced emission nanoparticles to the halloysite is (0.5-2.0):

100.

7. The preparation method according to claim 5, characterized in that: The concentration of the aggregation-induced luminescence nanoparticles is 0.01-10 mg / mL.

8. An application of the halloysite composite hemostatic material according to any one of claims 1 to 4, characterized in that: A suspension of halloysite composite hemostatic material is prepared, and then a medical non-woven fabric is immersed in the evenly stirred suspension, and the upper and lower edges are immersed once respectively; the immersed medical non-woven fabric is pressed and dried to obtain a halloysite hemostatic gauze.

9. The use according to claim 8, characterized in that: The concentration range of the suspension of the halloysite composite hemostatic material is 0.1-100 mg / mL.

Citation Information

Patent Citations

  • Large-aperture one-dimensional tubular zeolite and preparation method thereof

    CN104556098A

  • Dark red / near-infrared multifunctional aggregation-induced light-emitting material, preparation method and application thereof

    CN110790698A

  • Kaolin hemostatic gauze and preparation method thereof

    CN115463242A